Implementation of Digital Learning Media to Improve Student Learning Outcomes on Dry Skin Care Material: A Systematic Literature Review in Beauty and Vocational Education - Nurhayati, Ifa; Olivia, Alila; Mawalia, Annisa; Amalia, Ashiffa Fatikha; Mithalinda, Ayesha Nabila; Definta, Aufa Manda; Chairunnisa, Dhea Aprilia; Fitriani, Farida; Putri, Indah Selfiana; Legawa, Kayla Putri; Sarah, Kirana Alanis; Aulia, Khansa; Septriana, Nadilla; Listiana, Ridainisa Dwi; Nefi, Rosa; Hasanah, Selvi Hasnita; Queenasyifa, Queenasyifa (Universitas Negeri Semarang, 2025)
This study aims to examine the effectiveness of digital learning media in improving student learning outcomes on dry skin care materials. This research employed a systematic literature review (SLR) guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Literature searches were conducted across several academic databases, including Google Scholar, PubMed, IEEE Xplore, ScienceDirect, and Garuda, covering publications from 2016 to 2025. Following the screening and eligibility process, a total of 15 relevant articles (10 international and 5 national journals) were selected for analysis. The findings indicate that digital learning media—such as interactive videos, e-learning modules, mobile learning applications, and virtual simulations—consistently enhance students’ conceptual understanding, practical skills, and learning motivation in dry skin care education. The review also highlights that the effectiveness of digital media depends on instructional design quality, technological infrastructure, and educators’ readiness to integrate digital tools. Overall, the implementation of digital learning media through a blended learning approach is recommended to optimize learning outcomes in beauty and vocational education.